A SUMO Extension for Norm based Traffic Control Systems - Baumfalk, Jetze; Dastani, M.M.; Poot, Barend; Testerink, B.J.G. (Springer, 2018)
Autonomous vehicles will most likely participate in traffic in the near future. The advent of autonomous vehicles allows us to explore innovative ideas for traffic control such as norm based control systems. A norm is a violable rule that describes correct behavior. Norm based traffic control systems monitor traffic and effectuate sanctions in case vehicles violate norms. In this paper we present an extension of SUMO that enables the user to apply norm based control systems to traffic simulations. In our extension, vehicles are capable of making an autonomous decision on whether to comply with the norms or not. We provide a description of the extension, a summary on its implementation and an experimental evaluation.
Keywords: normative systems; distributed control; Taverne